2021
DOI: 10.1155/2021/6663989
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Influence of the Adsorbate Layer Composition on the Wetting of Different Substrates with Water

Abstract: Wetting is strongly influenced by adsorbate layers, which are omnipresent on surfaces. The influence of the composition and thickness of adsorbate layers on the water contact angle of sessile drops on different substrates was systematically investigated in the present work. Measurements were carried out for gold-sputtered substrates. These new results are compared to results from a previous study, in which corresponding measurements were carried out for technical steel and titanium substrates. In all experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 31 publications
1
12
0
Order By: Relevance
“…These findings are in good agreement with experimental data, which do not show any influence of the substrate on the wetting for adsorbate layers thicker than 1 – 2 nm; cf. ref .…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…These findings are in good agreement with experimental data, which do not show any influence of the substrate on the wetting for adsorbate layers thicker than 1 – 2 nm; cf. ref .…”
Section: Resultsmentioning
confidence: 99%
“…4 In most situations, the underlying substrate has no direct influence on the sessile drop when the adsorbate layer is thicker than about 1−2 nm. 5,6 In recent experimental studies on surfaces with adsorbate layer, that is, gold, steel, and titanium, Heier et al 2 observed that the contact angle depends only on the adsorbate layer composition for an adsorbate layer thicker than 1.4 nm. 1,2 In contrast, the wetting is influenced by the underlying substrate directly when the adsorbate layer is thinner than about 1 nm.…”
Section: ■ Introductionmentioning
confidence: 99%
See 3 more Smart Citations